INTENSITAS EFEKTIF SINYAL Wi-Fi DALAM RUANGAN TERTUTUP TERHADAP FUNGSI TERMODINAMIK - Zamri Zamri; Saktioto Saktioto (Universitas Riau, 2021)
Wi-Fi signal is an electromagnetic wave which in its transmission does not require an intermediary medium used in communication. But the intensity of the signal is influenced by the media it passes through. So in this article we will investigate how the signal propagation in a room is affected by the thermodynamic function. The treatment carried out is to show how the source point, namely the router and the receiver, namely the receiver, where later what is investigated is the trip to the position function, then a measurement will be carried out at that position which depends on changes in temperature and humidity in a closed room which is limited to the study. The source studied in the study was the signal strength intensity on the position, humidity and temperature functions. What is analyzed is the process of wave fluctuation at a certain time with varied data which will later be compared with other experimental results as a comparison, and will also show the signal intensity contour under normal conditions and conditions when the disturbance occurs.